THEORETICAL FRAMEWORKS AND COGNITIVE PRINCIPLES IN FOREIGN LANGUAGE ACQUISITION - Donisheva Gulruy Ahrorkulovna (Bright Mind Publishing, 2025)
Foreign language learning is deeply rooted in both pedagogical theories and psychological principles. Pedagogical foundations encompass instructional strategies, curriculum development, and assessment methods that facilitate effective language acquisition. Psychological foundations, on the other hand, explore cognitive processes, motivation, memory retention, and the role of affective factors in language learning. The methodical and psychological aspects of studying of a foreign language are examined in the article.
Keywords: Foreign language, factor, motivation, abilities, barrier.